2014
DOI: 10.2166/hydro.2014.034
|View full text |Cite
|
Sign up to set email alerts
|

Fish tracking in vertical slot fishways using computer vision techniques

Abstract: Vertical slot fishways are hydraulic structures which allow the upstream migration of fish through obstructions in rivers. The appropriate design of these devices should take into account the behavior and biological requirements of the target fish species. However, little is known at the present time about fish behavior in these artificial conditions, which hinders the development of more effective fishway design criteria. In this work, an efficient technique to study fish trajectories and behavior in vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
6
13
0
2
Order By: Relevance
“…In the studied conducted with VSF [90], efficiency of passage was size-related, as 74.1% (n = 60) of the individuals greater than 10 cm TL were able to ascend an experimental VSF with a flow of 100 L·s −1 , whereas only half of them (49.2%, n = 31) were only able to do it with a 250 L·s −1 flow. Similar results were also reported by other authors on the same experimental device [80], who found passage success was the lowest (33.3%) for the smallest individuals (10-15 cm TL), increasing with increasing of fish size-50% for individuals of 15-20 cm TL and further to 80.0% for individuals of 20-25 cm TL-and then decreased (41.2%) for the largest individuals (>25 cm TL). In this study, using computer vision techniques [80], fish tracking also showed that individuals avoided high-velocity areas and mainly used the recirculation regions in the upstream part of the pools, in which velocity and turbulence were lower, to move within the pools and for resting before ascending through the high velocity areas of the slots.…”
Section: Vertical Slot Fishways (Vsf)supporting
confidence: 91%
See 3 more Smart Citations
“…In the studied conducted with VSF [90], efficiency of passage was size-related, as 74.1% (n = 60) of the individuals greater than 10 cm TL were able to ascend an experimental VSF with a flow of 100 L·s −1 , whereas only half of them (49.2%, n = 31) were only able to do it with a 250 L·s −1 flow. Similar results were also reported by other authors on the same experimental device [80], who found passage success was the lowest (33.3%) for the smallest individuals (10-15 cm TL), increasing with increasing of fish size-50% for individuals of 15-20 cm TL and further to 80.0% for individuals of 20-25 cm TL-and then decreased (41.2%) for the largest individuals (>25 cm TL). In this study, using computer vision techniques [80], fish tracking also showed that individuals avoided high-velocity areas and mainly used the recirculation regions in the upstream part of the pools, in which velocity and turbulence were lower, to move within the pools and for resting before ascending through the high velocity areas of the slots.…”
Section: Vertical Slot Fishways (Vsf)supporting
confidence: 91%
“…Similar results were also reported by other authors on the same experimental device [80], who found passage success was the lowest (33.3%) for the smallest individuals (10-15 cm TL), increasing with increasing of fish size-50% for individuals of 15-20 cm TL and further to 80.0% for individuals of 20-25 cm TL-and then decreased (41.2%) for the largest individuals (>25 cm TL). In this study, using computer vision techniques [80], fish tracking also showed that individuals avoided high-velocity areas and mainly used the recirculation regions in the upstream part of the pools, in which velocity and turbulence were lower, to move within the pools and for resting before ascending through the high velocity areas of the slots. This preference of barbel for lower velocity and turbulence levels had also been observed for the NOF and OF designs (see previous sections) and is naturally expected since energy expenditures to maintain fish position are typically lower in such areas [104].…”
Section: Vertical Slot Fishways (Vsf)supporting
confidence: 91%
See 2 more Smart Citations
“…Entre ellas, cabe destacar el desarrollo de técnicas de visión artificial para el seguimiento de peces dentro de estos dispositivos (Rodríguez et al, 2015). Con estas nuevas aproximaciones se pretende contribuir a evaluar la respuesta de los peces a diferentes características hidráulicas, a definir los posibles factores clave en el remonte y a mejorar los modelos existentes para predecir la eficiencia de los dispositivos.…”
Section: Futuros Desarrollosunclassified